Perencanaan Scheduling dan Rescheduling dengan Metode Heuristic SPT Guna Meminimumkan Mean Tardiness dan Makespan - Eti Kristinawati (Department Industrial Engineering, University of Muhammadiyah Malang, 2002)
To complete customer's demand so company must make a plan with using production schedule. Some diffrculties usually happen in shop floor level is a new job which is put in a production schedule that have arranged before. So that the old production schedule have to revised by reschedulling. The procedure that be used to schedule the real time production consist of n job m machine is algoritm of Hueristik Dispatching Rule Shorted Processing Time (SPT) method to minimize mean tardiness and makespan.